2011
DOI: 10.1111/j.1745-6584.2011.00833.x
|View full text |Cite
|
Sign up to set email alerts
|

The Unusual and Large Drawdown Response of Buried‐Valley Aquifers to Pumping

Abstract: The buried-valley aquifers that are common in the glacial deposits of the northern hemisphere are a typical case of the strip aquifers that occur in many parts of the world. Pumping from a narrow strip aquifer leads to much greater drawdown and much more distant drawdown effects then would occur in a sheet aquifer with a similar transmissivity and storage coefficient. Widely used theories for radial flow to wells, such as the Theis equation, are not appropriate for narrow strip aquifers. Previously published t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…The magnitude of the drawdown at Queensville is estimated at approximately 30-35 m based on reported static water levels (ϳ240-245 m asl) from the MOECC water well record database in this area prior to 1960. This estimate is also consistent with pre-municipal pumping static groundwater levels in the area of approximately 245 m asl (International Water Consultants Ltd. 1977;Vallery et al 1982). The onset of YSA pumping in Aurora in the late 1950s would have affected any initial static water levels measured in this part of the YSA when the Queensville wells were drilled several decades later.…”
Section: Strip Aquifersupporting
confidence: 75%
“…The magnitude of the drawdown at Queensville is estimated at approximately 30-35 m based on reported static water levels (ϳ240-245 m asl) from the MOECC water well record database in this area prior to 1960. This estimate is also consistent with pre-municipal pumping static groundwater levels in the area of approximately 245 m asl (International Water Consultants Ltd. 1977;Vallery et al 1982). The onset of YSA pumping in Aurora in the late 1950s would have affected any initial static water levels measured in this part of the YSA when the Queensville wells were drilled several decades later.…”
Section: Strip Aquifersupporting
confidence: 75%
“…The types of lateral and vertical heterogeneity that characterize fan systems, including variations in grain size, porosity, mineralogy, lithologic texture, and channel body structure, will cause variations in hydraulic conductivity, storage, and porosity, and thus control flow and transport through the subsurface [ Fogg , ; Koltermann and Gorelick , ; Eaton , ]. Other studies of channel body aquifers have pointed out that ignoring the connectivity of permeable but spatially distinct channel deposits limits the ability to perform appropriate hydrogeological analysis [ Anderson , ; Fogg et al , ; Burns et al , ; Van der Kamp and Maathuis , ]. Renard and Allard [] showed that connectivity is a key influence on a wide range of groundwater flow and transport processes but is most important in areas with moderate proportions of aquifer bodies.…”
Section: Discussionmentioning
confidence: 99%
“…Downhole geophysics at Nobleton reveals coarsening-upward trends in gamma and conductivity logs where sand content increases slightly (Knight et al 2008); this is consistent with inferences from geophysical logs for Scarborough Formation northward from Lake Ontario bluffs (Eyles et al 1985). Organic or gas-rich strata intercepted in drilling, such as in aquifers near Schomberg and Alliston (Turner 1977), and in core (Hockley, Beeton, and Borden), is likely from Scarborough Formation (Bajc et al 2014; see more detail in Mulligan and Bajc 2018) or from Whitby Shale. However, previous correlation of Scarborough Formation to Vandorf (180 m asl), Ballantrae (210 m asl), and Newmarket (210 m asl) (Sharpe et al 2003) is now correlated within the elevation range for TF (<150 m asl) (Table 4).…”
Section: Scarborough Formation Inter-stadial Sediments?mentioning
confidence: 99%